Composite phaeochromocytoma with malignant peripheral nerve sheath tumour and rhabdomyosarcomatous differentiation in a patient without von Recklinghausen disease. Issue 7 (26th June 2009) - Gupta, R; Sharma, A; Arora, R; Vijayaraghavan, M
Abstract : The coexistence of adrenal phaeochromocytoma with non-chromaffin tumours is a rare fascinating occurrence. This category of tumours is subdivided into "composite" and "mixed". The coexistence of adrenal phaeochromocytoma with a malignant Triton tumour does not appear to have been described in the available literature so far. A unique case of composite phaeochromocytoma in a 26-year-old male patient, where the non-chromaffin component was a malignant Triton tumour composed of peripheral nerve sheath tumour and skeletal muscle differentiation, is reported. This admixture was confirmed with immunohistochemical pattern of expression. This is the first case of such a phenomenon in a composite phaeochromocytoma. The present case further widens the histomorphological range of composite phaeochromocytoma of the adrenal gland, which the histopathologist should be aware of. Since the prognosis of composite phaeochromocytoma with malignant nerve sheath tumour would be determined by the nerve sheath component, recognition of this tumour is imperative.